To tell or not to tell : the impact of Artificial Intelligence on impulsive buying and brand loyalty - Tomás, Alexandra Rosa (2021)
Due to the improvements in computing storage and fast speed of data processing machines, Artificial Intelligence (AI) sits at the core of what has been called the fourth industrial revolution. Different industries and sectors are starting to use AI to optimize their results, and among them, the marketers. They are now able to create a one-on-one marketing experience, providing close to perfect suggestions, and therefore, increasing impulsive buying and brand loyalty. Nevertheless, a paradox might exist due to consumers’ aversion towards algorithms. Thus, companies should know if revealing AI involvement in any marketing or selling effort is the best solution or if they should withhold this information. This dissertation experimentally explores this question by manipulating the involvement of an AI in a marketing campaign as well as its disclosure by the brand. The results suggest that consumers awareness of AI’s presence negatively impacts impulsive buying. Furthermore, the company should be the one informing consumers of its presence, otherwise, impulsive buying is further negatively affected. Unexpectedly, trust does not seem to mediate the results and brand loyalty appears to not be impacted by both variables. Results are discussed in light of recent advances on consumer reaction to AI.